Positive politeness strategies in expressing requests in the “School 2013” Korean television drama - Nikita Ayu Oktavianti; Herniwati Herniwati; Velayeti Nurfitriana Ansas (Universitas Pendidikan Indonesia (UPI), 2021)
Politeness in speech acts has been of great importance in social interaction to maintain the interpersonal relationship between the interlocutors. Nevertheless, research on how politeness strategies are conveyed in a particular speech act in a contemporary literary work is still lacking. This study aims to determine the forms of positive politeness strategies in directive speech acts with the requesting function. A descriptive qualitative was employed. The data were taken from directive speech with the function of requests contained in the television drama “School 2013”. A literature study method with listening and note-taking techniques was employed to analyze the data. This research particularly referred to Brown and Levinson’s theory of politeness strategies. The results showed that positive politeness sub-strategy 12 (include both Speaker and Hearer in the activity) were more widely used, namely 31 data (37%). The contributing factor is the frequent use of this utterance by the teacher to the students and speakers to their peers. By using positive politeness strategies, the speakers can show a sense of familiarity or a greater sense of care. It gives the impression that the speakers are on the same boat each other, and the request becomes of great importance for both interlocutors.